2017
DOI: 10.1002/cm.21405
|View full text |Cite
|
Sign up to set email alerts
|

ER/Golgi trafficking is facilitated by unbranched actin filaments containing Tpm4.2

Abstract: We have identified novel actin filaments defined by tropomyosin Tpm4.2 at the ER. EM analysis of mouse embryo fibroblasts (MEFs) isolated from mice expressing a mutant Tpm4.2 (Tpm4 ), incapable of incorporating into actin filaments, revealed swollen ER structures compared with wild-type (WT) MEFs (Tpm4 ). ER-to-Golgi, but not Golgi-to-ER trafficking was altered in the Tpm4 MEFs following the transfection of the temperature sensitive ER-associated ts045-VSVg construct. Exogenous Tpm4.2 was able to rescue the ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…The fact that basal proANP secretion by atrial myocytes lacking PAM resembled proANP secretion by Golgicide A-treated control myocytes suggested that inhibition of GBF1 prevented PAM from carrying out its normal role in the secretion of proANP by atrial myocytes, and that PAM affected proANP handling early in the secretory pathway. Blebbistatin, a myosin II-specific inhibitor (54), blocks tropomyosin 4.2-dependent ER to Golgi trafficking in mouse embryonic fibroblasts (55) and BFA-induced retrograde cis-Golgi to ER trafficking in pheochromocytoma cells (56). Blebbistatin had no effect on the rate at which proANP was secreted by either control or Pam Myh6-cKO/cKO myocytes (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…The fact that basal proANP secretion by atrial myocytes lacking PAM resembled proANP secretion by Golgicide A-treated control myocytes suggested that inhibition of GBF1 prevented PAM from carrying out its normal role in the secretion of proANP by atrial myocytes, and that PAM affected proANP handling early in the secretory pathway. Blebbistatin, a myosin II-specific inhibitor (54), blocks tropomyosin 4.2-dependent ER to Golgi trafficking in mouse embryonic fibroblasts (55) and BFA-induced retrograde cis-Golgi to ER trafficking in pheochromocytoma cells (56). Blebbistatin had no effect on the rate at which proANP was secreted by either control or Pam Myh6-cKO/cKO myocytes (Fig.…”
Section: Resultsmentioning
confidence: 90%
“…Tropomyosin Co-localizes with Most Actin Structures Tropomyosins have been implicated in a variety of different actin structures, including stress fibers [6], lamellipodia [7], granules [11], endosomes [12], cortical actin [13], the epithelial zonula adherens [14], podosomes [15], the cleavage furrow of dividing cells [16,17], mitotic spindles [16], actin ruffles [18], short microfilaments associated with the Golgi [16,19], filopodia [8], and the endoplasmic reticulum [20]. Mammalian cells can produce over 40 different splice variants using four different tropomyosin genes, TPM1-4, and the resulting gene products can be divided into low-molecular-weight (LMW) isoforms that span six actin monomers and high-molecular-weight (HMW) isoforms that span seven actin monomers.…”
Section: Resultsmentioning
confidence: 99%
“…The Arp2/ 3 complex NPF WHAMM can bind microtubules and membranes and is enriched at the ERGIC and cis-Golgi 140 , but recent studies have linked WHAMM more with autophagy 141,142 . Other recent findings have implicated a specific population of tropomyosin 4.2-coated actin filaments as being important for ER-to-Golgi trafficking in a manner independent of Arp2/3 complex, but dependent on myosin II 143 . More work is needed to define actin polymerization factors and their roles in ER-to-Golgi transport.…”
Section: Actin and Er Structure/functionmentioning
confidence: 95%